Efforts to Prevent Scabies Through Improving Sanitation at the Darul Qur'an Islamic Boarding School in Cimalaka - Evi Sonjati; Resti Restiawati (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Scabies is a skin disease caused by infestation with the mite Sarcoptes scabiei var. hominis. This disease can spread quickly in an unhygienic environment. Islamic boarding schools are places where many individuals live in one dense environment, thereby increasing the risk of transmission of scabies. This research aims to improve sanitation at the Darul Qur'an Cimalaka Islamic Boarding School as an effort to prevent scabies. The method used was direct observation of the sanitary conditions in Islamic boarding schools, as well as counseling and training for Islamic boarding school residents regarding the importance of maintaining personal and environmental cleanliness. The results of the research showed that there was a significant improvement in environmental cleanliness in Islamic boarding schools after sanitation interventions were carried out. Apart from that, the knowledge and awareness of Islamic boarding school residents about the importance of maintaining cleanliness also increased significantly after counseling and training. In conclusion, increasing sanitation and awareness about the importance of maintaining personal and environmental cleanliness can be effective in preventing the transmission of scabies at the Darul Qur'an Cimalaka Islamic Boarding School. Preventive measures like this can be implemented in other Islamic boarding schools to reduce the risk of infectious diseases in crowded environments such as Islamic boarding schools